KINERJA KEUANGAN KPRI ADHY KARYA DI KABUPATEN BREBES DITINJAU DARI RASIO LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS - Purwanto, Medi Tri (PERMANA, 2013)
This study aims to determine the financial performance of KPRI Adhy Karya inKabupaten Brebes in 2008 - 2010 based on analysis of the liquidity ratio, solvency, and profitability ratios. Data analysis in this study uses : quantitative analysis techniques that illustrate the financial performance KPRI Adhy Karya Kabupaten Brebes with liquidity ratios, solvency ratios, and profitability ratios. The results showed that the measurement of financial performance KPRI Adhy Karya Kabupaten Brebes less well expressed. This is evident from their own capital profitability in the classification is quite good, so it can be stated that the performance of the work Adhy KPRI Brebes to generate profits from its own capital is quite good . Profitability ratios during the period 2008 to 2010 were classified as very good, so it can be stated that the performance of cooperatives both in generating profits from every revenue received for each period. Liquidity ratios are classified under unfavorable conditions during the period 2008-2010 due to liquidity ratios are too high. This may imply that the amount of current assets over current liabilities are too high, thus indicating that the performance of co-operatives in the use of the current assets. Solvency of cooperative performance is expressed in the classification that is not good, because the ratio is too high during the period 2008-2010. This may imply that the cooperative has not been able to put forth maximum owned assets and the ratio of equity capital to debt classified in the unfavorable conditions. Numbers indicate the ratio is too high not to maximize the use of cooperative equity in operations optimally. The implications of this research work is KPRI Adhy Karya Kabupaten Brebes to better maximize the use of current assets to current assets that are not too high compared to the total current debt . Way to do them with more debt in order to improve the management of accounts receivable amount is not too big and not cooperative because of bad debt losses . In addition it should be more cooperative arrange the smooth sale of inventory that is not excessive amount of inventory as well as the cooperative should be able to use the cash held for the benefit for cooperative activities, for example, invested in certain assets so as to obtain benefits and maximize the use of fixed assets and equity that the proportion of the total capital and assets against total debt is not too large. Way to do is to add or commercialize the use of assets in the operational activities of cooperatives in order to better benefit the cooperative. Activities to do such as the inclusion of others participating in the cooperative or other business which the cooperative can provide benefits to the cooperative level. Keywords : Financial Ratios , Financial Performance.